Comparison of the yield of tuberculosis among contacts of multidrug-resistant and drug-sensitive tuberculosis patients in Ethiopia using GeneXpert as a primary diagnostic test. (June 2018) - Hiruy, Nebiyu; Melese, Muluken; Habte, Dereje; Jerene, Degu; Gashu, Zewdu; Alem, Genetu; Jemal, Ilili; Tessema, Belay; Belayneh, Beza; Suarez, Pedro G.
Highlights: Using GeneXpert in testing of presumptive DS TB/MDR TB contacts has shown considerable yield with more RR TB cases diagnosed among MDR TB contacts than DS TB contacts. The use of GeneXpert in DS TB contact investigation has an added advantage of diagnosing RR cases in contrast to using the nationally recommended AFB microscopy for DS TB contact investigation. The finding in this study can serve as a reference in TB case finding planning and evaluation in Ethiopia and similar settings. Abstract: Objectives: This study compared the yield of tuberculosis (TB) among contacts of multidrug-resistant tuberculosis (MDR-TB) index cases with that in drug-sensitive TB (DS-TB) index cases in a program setting. Methods: A comparative cross-sectional study was conducted among contacts of sputum smear-positive new DS-TB index cases and MDR-TB index cases. After contacts were screened, GeneXpert was used for the diagnosis of TB. Results: The study included 111 MDR-TB and 119 DS-TB index cases. A total of 340 and 393 contacts of MDR-TB and DS-TB index cases, respectively, were traced, of whom 331 among MDR-TB contacts and 353 among DS-TB contacts were screened. There were 20 (6%) presumptive TB cases for MDR-TB contacts and 41 (11%) for DS-TB contacts. The prevalence of TB among MDR-TB contacts was 2.7% and among DS-TB contacts was 4.0%. The majority of the MDR-TB contacts diagnosed with TB had MDR-TB; the reverse was true for DS-TB. Conclusions: The yield of TB among contacts of MDR-TB and DS-TB patients using GeneXpert was high as compared to the population-level prevalence. The likelihood of diagnosing rifampicin-resistant TB among contacts of MDR-TB index cases was higher in comparison with contacts of DS-TB index cases. The use of GeneXpert in DS-TB contact investigation has the added advantage of diagnosing rifampicin-resistant TB cases when compared to the use of the nationally recommended acid-fast bacillus (AFB) microscopy for DS-TB contact investigation.